Transcriptome Analysis of Ovary Development in Nile Tilapia Under Different Photoperiod Regimes - Tang, Zhanyang; Zhou, Yi; Xiao, Jun; Zhong, Huan; Miao, Weiwei; Guo, Zhongbao; Zhang, Xu; Zhou, Lei; Luo, Yongju (Frontiers in Genetics, 2019)
This study investigated the molecular mechanisms involved in ovarian transcriptomic responses in Nile tilapia under different photoperiod regimes. Histological analysis indicated that ovarian development was significantly affected by photoperiod. The photoperiods tested were as follows: LD (12 h light:12 h dark), LL (24 h light:0 h dark), and DD (0 h light:24 h dark). The longer photoperiod (LL) was shown to induce ovary development earlier than LD and DD. Next, ovary transcriptome levels were sequenced and analyzed. These data indicated that 988, 992, and 1,036 differentially expressed genes (DEGs) were detected by comparing LD–LL, LD–DD, and LL–DD. A number of genes that may be involved in photoperiod-specific regulation of ovarian development were observed. These findings may be useful for investigating the molecular mechanisms underlying light-induced ovarian development in Nile tilapia.